If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5y + -10) + 2(3y + 8) = 0 Reorder the terms: -3(-10 + 5y) + 2(3y + 8) = 0 (-10 * -3 + 5y * -3) + 2(3y + 8) = 0 (30 + -15y) + 2(3y + 8) = 0 Reorder the terms: 30 + -15y + 2(8 + 3y) = 0 30 + -15y + (8 * 2 + 3y * 2) = 0 30 + -15y + (16 + 6y) = 0 Reorder the terms: 30 + 16 + -15y + 6y = 0 Combine like terms: 30 + 16 = 46 46 + -15y + 6y = 0 Combine like terms: -15y + 6y = -9y 46 + -9y = 0 Solving 46 + -9y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-46' to each side of the equation. 46 + -46 + -9y = 0 + -46 Combine like terms: 46 + -46 = 0 0 + -9y = 0 + -46 -9y = 0 + -46 Combine like terms: 0 + -46 = -46 -9y = -46 Divide each side by '-9'. y = 5.111111111 Simplifying y = 5.111111111
| -6/-12 | | 11x+9=5x-33 | | 3+21/2 | | (-4/3)x(1/5)=-5 | | (49x^4y^6z^10)^(1/2) | | 6x+12=3x+21 | | (-8)(-4)(0)= | | 4x=-25-6x | | 1.4+(0.9)= | | x-2/4=5 | | y^3+4y^2+6y+4=0 | | 3(5x-10)=20x | | 2x=-7x+18 | | 12y-18x=18 | | 10n=7n+7+2n | | 9x-(3*7)=6 | | 5000x=250+20x | | y^2+14y+27=0 | | 7-2(f+3)=2(4-3f) | | -2x+7=28 | | 3(8-5)-3(16+12)= | | X-4-3x=-2x+5-1 | | 4x-21+7x-3=9x-11+3x | | 6u^2-u-1=0 | | 6p+13=31 | | 3x+12y=51 | | 5m+12+2m=2m+18-5 | | -4.9+x=11.3 | | (6x-11)/2x | | 4a-(a-2)=19+3a | | -12x+3x-202=59 | | 6+4a=16+2a |